O Movimento Bandeirante entre tensões e contradições: a reformulação institucional de 1968 - Fellini, Mariella (Universidade do Vale do Rio dos Sinos, 2017)
The Movement, in Brazil called Bandeirante, was created in England in 1909 by Robert Baden-Powell, a military officer. Originally nominated Girls Guides, this movement only congregated girls, while its counterpart Boys Scouts was for boys exclusively. In 1919, the Bandeirantismo was first introduced in Brazil by members of Rio de Janeiro’s elite that had been engaged in it in Europe. The activities were then focused in the education of girls that should learn how to interpret their gender roles properly. In its first decades, the Movement expanded across the country, strongly supported by State and Catholic Church. Conservative by nature, the Movement kept its characteristics until 1960’s, when a decrease in its members indicated the immediate need of reformulation. The aim of this dissertation is to evaluate the 1967-68’s restructuring of Bandeirante Movement, observing tensions, contradictions and possible limitations to the Movement’s innovation. The empirical basis of the study was the Reformulation Report of the Federação de Bandeirantes do Brasil, that seek to point out the existing problems as well as to suggest reformulations that could overcome possible anachronisms. Likewise, Bandeirantes magazine was consulted, and its reading throughout the 1960’s decade made possible to distinguish different opinions from the most variate levels, such as directory and regular participants, about the problems inside the Movement. Finally, the minute of several national conferences were consulted, in which the conceptions and actions of the Guidism in Brazil was discussed, especially after its official transformation in a mixed movement, in 1968. The analytic categories that substantiate these documents reading was: conservatism, defined by the reading of Norberto Bobbio; gender, based on the discussions of Joan Scott; liberal feminism, through the studying of Celi Pinto; and coeducation, based on the discussions of Aldenise Santos and Dinamara Feldens. As results, was presented the main contradictions of the Movement, that precluded more profound innovations and kept a predominantly conservative institutional culture, even though surrounded by speeches and practices that, sometimes, could be considered progressive.
Keywords: Movimento bandeirante; Conservadorismo; Reformulação Istitucional do Movimento Bandeirante; Bandeirante Movement; Conservatism; Institutional Reformulation of Bandeirante Movement; ACCNPQ::Ciências Humanas::Educação